(untitled) (Journal of Lithic Studies, 2016)
The basins of the Manzanares and Jarama rivers have been connected to human activity since the early Palaeolithic. At the boundary between these rivers the abundance of flint has given place to exploitation and mining activities even in historical times. In recent years, projects related to urban expansion in the southeast of Madrid have brought to light various Palaeolithic deposits associated with workshops and tool production. These sites do not have evidence of river pebbles of quartzite, quartz or sandstone in the immediate environment that could have been used as hammerstones, meaning that hammerstones in these raw materials had to be transported and introduced into the sites from large distances. Given this situation, attention was paid to flint elements that show clear signs of being used as hammerstones. The aim of this study is to test the effectiveness of flint as hammerstone, testing whether the use of this raw material is indifferent to other rock types or if you have limitations or advantages in this regard. An experimental protocol was developed, allowing to observe specific knapping behaviours and justifying them in the archaeological and technological context in which they are located.